PERILAKU COMPULSIVE BUYING PADA REMAJA DI KOTA BANDUNG DALAM PERSPEKTIF SOSIOLOGI EKONOMI - Arifianti, Ria; Putri Firsanty, Farah (JURNAL LENTERA BISNIS, 2026)
The phenomenon of shopping is an interesting topic from a social and economic perspective. Modern developments have given rise to different perceptions and goals of shopping. One such phenomenon is compulsive buying. This article aims to explain how compulsive buying is practiced by teenagers in Bandung. This paper aims to describe concrete examples and forms of adolescent shopping behavior in Bandung, which demonstrate repetitive behavior to gain certain social status and recognition in society. This study uses Solomon's theory of compulsive buying and James Coleman's theory of rational choice, which states that compulsive buyers are those who like to spend their money on things they don't need. Compulsive buyers will feel anxious if their desires are not fulfilled or if the desired item cannot be purchased. In economic sociology, compulsive buying, which is part of the economic process of consumption, can be analyzed using James Coleman's Rational Choice Theory on the phenomenon of compulsive buying among urban adolescents in Indonesia, offering an interesting perspective: behavior that seems irrational (wasteful/impulsive) is actually a rational and planned action to achieve certain social goals. This descriptive research aims to create a systematic, factual, and accurate description or picture of compulsive buying among adolescents in Bandung City. Based on the analysis, James Coleman believes that compulsive buying among Bandung teenagers is a strategic investment for survival in a city ecosystem that prioritizes the aesthetics of creativity. They exchange their pocket money for validation as contemporary or urban youth. They seek access to creative social circles and a sense of security from the stigma of being out of date in exchange for social recognition within certain friendship circles.